2016
DOI: 10.5946/ce.2016.132
|View full text |Cite
|
Sign up to set email alerts
|

Painless Colonoscopy: Available Techniques and Instruments

Abstract: During colonoscopy, air insufflation to distend the lumen and facilitate careful inspection and scope insertion can induce pain and cause discomfort. Carbon dioxide (CO2) insufflation can decrease abdominal pain and discomfort during and after colonoscopy. The advantage of CO2 insufflation is the rapid absorption of the gas across the intestine. Another painless option is water-assisted colonoscopy. Two methods for water-assisted colonoscopy are available: water immersion and water exchange. In a recent direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Excessive mesentery stretching may increase the risk of mesenteric tear and bowel perforation during insertion. [ 3 ] In the present study, 91.1% of patients acquired painless intubation (VAS = 0), the VAS score of other patients is 1-2 points. These findings suggested that using transnasal gastroscope for colon examination was almost painless and was very safe.…”
supporting
confidence: 46%
“…Excessive mesentery stretching may increase the risk of mesenteric tear and bowel perforation during insertion. [ 3 ] In the present study, 91.1% of patients acquired painless intubation (VAS = 0), the VAS score of other patients is 1-2 points. These findings suggested that using transnasal gastroscope for colon examination was almost painless and was very safe.…”
supporting
confidence: 46%
“…CO 2 insu ation induces less postprocedural pain compared with nitrogen due to more rapid absorption. (20) The incidence of cardiorespiratory events were similar in both groups. Hypoxia secondary to respiratory depression and airway obstruction is the most frequent complication of PSA during colonoscopy.…”
Section: Discussionmentioning
confidence: 77%
“…[ 24 , 25 ] This technique can be tried in unsedated patients with IDS > 1. Secondly, CO2 insufflation, the use of small-caliber endoscopes or cap-assisted colonoscopy [ 26 ] may be helpful to alleviate pain. Lastly, sedation can ensure patients painless during the whole procedure.…”
Section: Discussionmentioning
confidence: 99%